Tropicoporus stratificans sp. nov. (Hymenochaetales, Basidiomycota) from southern Brazil - Coelho, Gilberto; Silveira, Andressa De Oliveira; Antoniolli, Zaida Inês; Yurchenko, Eugene (Phytotaxa, 2016)
Tropicoporus is a recently proposed genus that was segregated from Inonotus s.l. and includes species with important wood decay and medicinal functions. The description of T. stratificans sp. nov. is based on more than 10 specimens collected on fallen decayed wood in subtropical forests of Rio Grande do Sul State. The species is recognized by its resupinate, poroid, golden brown, perennial basidiomes that become multi-layered, dimitic hyphal system, abundant hymenial setae, and subglobose to ellipsoid, brownish-yellow to ferruginous-brown basidiospores. Based on nrDNA ITS sequences, Bayesian and maximum likelihood phylogenetic analyses of Tropicoporus nested the new taxon in the T. linteus clade. A description and illustrations of the new species are provided.